A Hard Look in the Mirror: Re-imagining the Role of the Librarian at the Greater Victoria Public Library. Issue 1 (2nd January 2023) - Kendrick, Tracy; Rowan, Jennifer; Windecker, Jennifer
ABSTRACT: As an urban Canadian public library system, Greater Victoria Public Library was not alone in trying to define the role of librarians within the context of a changing digital landscape and a reality where patrons were no longer seeking out librarians for in-depth reference questions at a traditional reference desk. Situated on Vancouver Island in the southwest corner of British Columbia, Canada, GVPL is a multi-branch system that was looking for ways to define the role of librarians within branches, within the organization, and within the library sector as a whole. By creating a community-inspired model with librarians as leaders within portfolios rather than defined by the ages that they were delivering programs for, GVPL developed a framework for community engagement with librarians as key drivers in the ensuring the library remains innovative, sustainable and valued.